2022
DOI: 10.21037/atm-21-7032
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cancer-promoting genes related to chemotherapy resistance in esophageal squamous cell carcinoma

Abstract: Background: According to histopathology, esophageal cancer can be divided into squamous cell carcinoma (SCC) and esophageal adenocarcinoma (adeno arcinoma). In China, 90% of esophageal cancer patients are squamous cell carcinoma. Cisplatin and fluaziridine are the main chemotherapy before and after surgery.Long-term drug treatment is often accompanied by the emergence of drug resistance of tumor cells. There are many mechanisms for the emergence of drug resistance of tumor cells, including the increase of drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…We identified BMP1 and TPM2 as promising universal candidate biomarkers for identifying chemoresistant patients before treatment when using bulk transcriptome data. Both genes can facilitate chemoresistance (36,37), supporting the rationality of our analyses.…”
Section: Discussionsupporting
confidence: 80%
“…We identified BMP1 and TPM2 as promising universal candidate biomarkers for identifying chemoresistant patients before treatment when using bulk transcriptome data. Both genes can facilitate chemoresistance (36,37), supporting the rationality of our analyses.…”
Section: Discussionsupporting
confidence: 80%
“…The drug resistance/response mechanism of ESCC is very complicated. A study found that differential genes are also key cancer-promoting genes related to chemotherapy resistance through PPI, such as BMP1 and DBF4 ( 56 ); prognosis-related genes, such as TTK and KIF18A . These studies can help improve the survival rate of patients ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Computer-aided diagnosis ( 79 ) and computer-aided therapy ( 80 ) have become the main application directions, and deep learning (#5) has emerged as the name of specific methods of artificial intelligence with the highest word frequency13.89 ( Figure 8D ). Specifically, deep learning plays a role in early detection ( 81 ), accurate differentiation of precancerous lesions from tumor lesions ( 82 ), determination of invasive tumor margins during surgical treatment ( 83 ), monitoring of disease progression and acquired drug resistance ( 84 ), and prediction of tumor aggressiveness ( 85 ), metastasis pattern ( 86 ) and recurrence risk ( 87 ). The innovation of esophageal imaging recognition and cancer marker screening technology provides the possibility for esophageal cancer detection, treatment and monitoring.…”
Section: Discussionmentioning
confidence: 99%